To find an expression that has the same sum as \(-12 + 4\), let's first calculate the result of \(-12 + 4\):
\[ -12 + 4 = -8 \]
Now, we need to evaluate the provided options to see which also equals \(-8\):
-
\(12 + 4\): \[ 12 + 4 = 16 \] This is not equal to \(-8\).
-
\(4 + (-12)\): \[ 4 + (-12) = 4 - 12 = -8 \] This is equal to \(-8\).
-
\(12 + (-4)\): \[ 12 - 4 = 8 \] This is not equal to \(-8\).
-
\(-4 + (-12)\): \[ -4 - 12 = -16 \] This is not equal to \(-8\).
The only expression that has the same sum as \(-12 + 4\) is:
\(4 + (-12)\).